Celebrities and cyber crimes: An analysis of the victimization of female film stars on the internet - Halder Debarati; Jaishankar Karuppannan (Temida)
With the advent of internet and digital communication technology, online crimes targeting celebrities have gained a momentum. This article argues that, among the celebrities, actresses of Hollywood and Bollywood are particularly targeted online mainly because of their sex appeal and easy availability of contents including their images, video clippings, their private geo-location information, etc. The perpetrators are mostly fans who may wish to view the actresses as sex symbols. This article suggests that production houses should take primary responsibilities to prevent such victimisation and the actors themselves may avail legal policies such as right to be forgotten to approach the internet companies including search engines like Google to prevent victimisation and remove the offensive contents.